A research study on the preferences of personnel manager of selected private firms in Iloilo City in hiring their employees - Daquilanea, Leonie; Paderna, Annabelle; Torrecampo, Sharon Grace
The problem of getting a job has always been a dilemma faced by graduates. The preferences of personnel managers in hiring employees really matter. This study then, seeks to determine the preferences of personnel managers and the most prioritized factor in each different business sector. Another is to determine the choices of private firms specifically banks/financial institutions, auditing firms, airlines, service companies, and merchandising companies in hiring their employees. This study was conducted in Iloilo City proper with the hiring committee/personnel managers of different private firms having a localized hiring process. Out of seventy-two respondents only six of them responded to the survey. The questionnaires were the only instrument employed by the researchers to gather data.With the data gathered, the researchers analyzed them using the frequency distribution, descriptive statistics, spearman rank correlation chi-square test. The result and findings were presented according to how they answer and respond the objectives of the researchers. Based on the results and finding of the study, the preferences of personnel managers in hiring applicants is based on their interview rating, followed by satisfactory scholastic record, and commendable examination results.